2017
DOI: 10.1002/prep.201700155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Organic‐inorganic Nanocomposite Additive on the Combustion and Erosion Performance of High Energy Propellants Containing RDX

Abstract: A nanocomposite microsphere consisting of solid paraffin, nano-TiO 2 , nano-BN, zeolitic imidazolate framework-67 particles and polymethyl methacrylate was prepared and applied as a functional additive for high energy propellants (with about 23 wt % RDX) to reduce the barrel erosion and improve its combustion performance as well. High energy propellants modified with the nanocomposite were manufactured by a solvent extrusion technique. According to the scanning electron microscope and differential scanning cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Various factors affect the burning rate of propellants, such as the particle diameter, oxidizer species, pressure, and temperature etc. [29]. This might be related to the increase of burning rate of propellants with CL-20 in the high pressure range.…”
Section: Full Papermentioning
confidence: 93%
“…Various factors affect the burning rate of propellants, such as the particle diameter, oxidizer species, pressure, and temperature etc. [29]. This might be related to the increase of burning rate of propellants with CL-20 in the high pressure range.…”
Section: Full Papermentioning
confidence: 93%
“…In this paper, the erosion effect of the composite microcapsules that fills up the propellant charging system can be expressed by anti-erosion efficiency (E) which can be calculated by the following two equations [20]:…”
Section: Anti-erosion Effect Of Composite Silicone Oil Microcapsulesmentioning
confidence: 99%
“…Overall it has been gathered from the literature that high energy materials such as RDX, HMX, FOX-7, and CL-20, when used in propellants, have given promising results. Reduced vulnerability, better output, and higher burning rate are some of the characteristics incorporated in the propellant compositions on the inclusion of high-energy materials [16][17][18]. In a recent study Wang et al [19] reported that burning rates of composite modified double base (CMDB) propellants increased substantially with the addition of CL-20 and decreased with the addition of RDX.…”
Section: Introductionmentioning
confidence: 99%
“…Overall it has been gathered from the literature that high energy materials such as RDX, HMX, FOX‐7, and CL‐20, when used in propellants, have given promising results. Reduced vulnerability, better output, and higher burning rate are some of the characteristics incorporated in the propellant compositions on the inclusion of high‐energy materials [16–18]. In a recent study Wang et al.…”
Section: Introductionmentioning
confidence: 99%